Knowledge Management and Education in the Context of Innovation: A Bibliometric Analysis - Setiana, Dafid Slamet; Fitriana Tjiptasari; Endang Sri Budi Herawati; Erma Kusumawardhani; Gumpanat Boriboon (Faculty of Educational Sciences, Universitas Negeri Yogyakarta, 2026)
This study aims to synthesize a corpus of publications on knowledge management, higher education, and innovation through bibliometric analysis to understand research trends, outcomes, and impacts in these fields. The method employed is a quantitative analysis of bibliographic data sourced from the Scopus.com database for the period from 2013 to 2022. A search using the keywords “knowledge management,” “higher education,” and ‘innovation’ yielded a total of 196 documents. The results indicate that publications peaked in 2019 but declined during the COVID-19 pandemic from 2020 to 2022. The subject of “computer science” dominated contributions to innovation through knowledge management. Network analysis successfully identified four main research clusters covering the elements of e-learning, educational leadership, management information systems, and human resource management. The main conclusion of this study is that research on the application of knowledge management processes to create innovation in the field of education is still rarely conducted in Scopus-indexed articles, thus opening up significant opportunities for researchers to explore this topic in the future.